The omega -3 and omega-3 index blood levels and their association with demographic, clinical characteristics, fasting blood sugar and lipid profiles among health staffs population - Musa, Kamarul Imran (Universiti Sains Malaysia, 2015)
Two important types of Omega 3 fatty acids arc the Eicosapentaenoic Acid (EPA) and Docosahexaenoic Acid (DHA). The main sources of EPA and DHA come from the marine life species. Both EPA and DHA are linked with the protection from cardiovascular risk factors, inflammatory related diseases and neuro-psychology diseases in human. This study aimed to assess the levels of EPA and DHA in selected marine and fresh-water species of fishes and shellfish found in the east coast of Peninsular Malaysia. Next, the study aimed to measure the blood levels of EPA and DHA in health workers in the state of Kelantan, Malaysia and their important related factors A cross sectional study was done. It was divided into two parts; 1) to assess the level of EPA and DHA in selected marine and fresh water species of fishes and shellfish found along the east coast of Peninsular Malaysia and 2) to measure the blood levels of EPA and DHA in the randomly selected health workers in the state of Kelantan. The relationship between the levels of EPA and DHA with the socio-demography profiles, health status, knowledge level, physical activity, anthropometry measurement and blood biochemical profiles were also assessed. The levels of EPA and DHA were measured from a total of 14 species of marine fish, 3 species of freshwater fish, 4 species of shellfish and 2 commercially canned fish. In addition, a total of 380 randomly selected health workers from 4 selected health premises in the state of Kelantan from the period of June 2010 until September 2010, answered a set of questionnaire, their anthropometry were measured and blood samples were taken. The blood samples were analyzed to determine the level of EPA and DHA and other cardiovascular biomarkers. The fat contents of the marine fish species, the freshwater fish species and shellfish ranged from 1.01% to 15.83%. Most fishes in the study have shown that their fat contents were beyond 10% of their body weight while their DHA levels were higher than the EPA levels. The study on the health workers showed that the mean level of DHA was 25.9 pg/ml (SD 27.07) while the mean level of EPA was 2.3 pg/inl (SD 1.58). Our analysis showed that the EPA level (mean 3.5 pg/ml, SD 1.93) and the DHA level (mean 40.1 pg/ml. SD 25.46) were higher among the medical doctors compared to the other categories of health workers. The levels of EPA (mean 2.8 pg/ml, SD 1.91) and DHA (mean 40.1 pg/ml, SD 25.46) were higher among the health workers with higher level of education. The physical activities, anthropometry measurements and levels of biochemical profiles were not i related with the levels of EPA and DHA. i The level of EPA was significantly higher in the health workers with higher score of knowledge in Omega 3 compounds and their benefits (adjusted mean 2.8 pg/ml) after we have adjusted the effect of the confounding variables. The > level of DHA was also higher in this group of health workers (adjusted mean ) 37.5 pg/ml). All species of fishes and shellfishes found in the east coast region of Peninsular Malaysia selected in our study are the important sources for EPA and DHA. The health workers with higher knowledge of Omega 3 have higher blood level of Omega 3. Health promotion activities to promote the knowledge about the sources of EPA and DHA are important in the future. Healthy lifestyle practice which includes taking sources with high EPA and DHA contents will be beneficial for good health.